The Impact of the Introduction of a Carbon Tax for Scotland - Patrizio Lecca; Grant Allan; Peter McGregor; Kim Swales (European Regional Science Association (ERSA), 2013)
Since devolution, the Scottish Government has increasingly adopted a distinctive environmental and energy policy (Allan et al., 2008). The Climate Change (Scotland) Act includes a target to reduce CO2 emissions to 42% below 1990 levels by 2020. This is stricter than the 34% CO2 emissions reduction adopted by the UK Government. Moreover, the corresponding Scottish Government target for renewable electricity generation in 2020 is equivalent to 100% of electricity consumption in Scotland and preliminary data suggest that the interim 2011 target of 31% was exceeded by 4 percentage points. However, earlier discussions have established that whilst Scotland has adopted challenging targets, many key policy instruments are reserved to the UK government (Allan et al., 2008; McGregor et al., 2011). At present the main ?green? elements of the tax system remain under Westminster control. This includes fuel duties, air passenger duty and the climate change levy. By and large economists regard a carbon tax as the most efficient way to reduce carbon emissions (Tullock, 1967; Pearce, 1991). It is therefore of interest to consider the effect of a Scottish specific carbon tax. This is particularly relevant given the more demanding environmental targets set by the Scottish Government and the present discussions around increased fiscal autonomy for Scotland. The Scotland Act (2012) has augmented the income tax raising power of the Scottish Parliament who has now the power to make a balanced-budget adjustment in public expenditure funded by corresponding changes in the basic as well as higher rates of income tax of up to 10p in the pound . In this paper we therefore use an empirical energy-economy-environmental model of Scotland to simulate the impact of the Scottish Government imposing such a tax on carbon emissions and the level of aggregate activity. Given the present constitutional adjustment, from the existing distortionary taxes the Scottish Government has the power to make only adjustment to the labour income tax. Thus, the simulation exercises consist of introducing a tax on energy consumption by firms through a reduction in labour income tax and a cut in current government expenditure.
Keywords: 330